CORRELATION BETWEEN PREPARATION DOING TASKS OF LECTURING AND PREPARATION FACING FINAL EXAM (A Study of Students’ Habit in Learning) - Sudiyono Sudiyono (PROJECT (Professional Journal of English Education), 2020)
This research was about correlation between doing tasks of lecturing (X variable) and doing preparation facing final exam (Y variable). Data used in this research was the students of English Program of STKIP Siliwang Bandung, Semester VII academic year 2015-2016. The research concerns to find out the correlation between two variables observed, preparation doing tasks of lecturing and preparation facing the final exam. To achieve the most accurate results of this research, here researcher choose correlational method. The results of this research shown mean of X variable was 4.30 and mean of Y variable was 4.36. They mean that both activities (doing tasks of lecturing (X variable) and doing preparation facing final exam (Y variable) are high/good. But, the correlation between them was low/not significant, it was indicated by 0,23 scale of Likert. Keywords:  Lecturing, Tasks, Final Exam